The impact of closing schools on working from home during the COVID-19 pandemic: evidence using panel data from Japan - Yamamura, Eiji (Rev Econ Househ, 2021)
COVID-19 has led to the closure of various schools in Japan to cope with the pandemic. This study explores how school closure influences parents’ work style based on short panel data for the period of school closure from mid-March to mid-April 2020. Specifically, we analyze how the presence of their children influences parents’ work at home and examine how the effect differs by the parent’s gender. After controlling for various factors, we find that in cases where parents are full-time employees and the children are: (1) in primary school, mothers are more likely to work remotely, while fathers are less likely to do so and (2) in junior high school, the parents’ work styles are hardly affected. This shows that mothers shoulder the burden of working remotely and caring for small children at home, while fathers tend to work in the office and spend less time with their childcare at home. Inevitably, COVID-19 has increased the inequality in the burden of child care.